2021
DOI: 10.1093/icesjms/fsab127
|View full text |Cite
|
Sign up to set email alerts
|

Oceanographic structure and seasonal variation contribute to high heterogeneity in mesozooplankton over small spatial scales

Abstract: The coastal oceans can be highly variable, especially near ocean fronts. The Ushant Front is the dominant oceanographic feature in the Iroise Sea (NE Atlantic) during summer, separating warm stratified offshore waters from cool vertically-mixed nearshore waters. Mesozooplankton community structure was investigated over an annual cycle to examine relationships with oceanographic conditions. DNA metabarcoding of COI and 18S genes was used in communities from six sites along two cross-shelf transects. Taxonomic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 73 publications
1
3
0
Order By: Relevance
“…RDA results showed that IC, SCM, SST, SSS, and DO were key environmental factors impacting meroplankton community structure (Figure 6). It was consistent with previous studies (Silberberger et al, 2016;Brandão et al, 2020;Brandão et al, 2021). Many studies have shown that meroplankton mostly feeds on algae (Conover, 1968;Paulay et al, 1985;Fenaux et al, 1994).…”
Section: Meroplankton Geographical Distribution Patternsupporting
confidence: 93%
“…RDA results showed that IC, SCM, SST, SSS, and DO were key environmental factors impacting meroplankton community structure (Figure 6). It was consistent with previous studies (Silberberger et al, 2016;Brandão et al, 2020;Brandão et al, 2021). Many studies have shown that meroplankton mostly feeds on algae (Conover, 1968;Paulay et al, 1985;Fenaux et al, 1994).…”
Section: Meroplankton Geographical Distribution Patternsupporting
confidence: 93%
“…Habitat heterogeneity provides more diversified resources (Evans et al, 2005; La Mesa et al, 2011) that can be used by a wider range of functionally distinct species performing specific key functions in the ecosystem (Mouillot et al, 2013). Moreover, the proximity of the Ushant tidal front offshore the Chaussée de Sein, occurring in summer in the Iroise Sea (Schultes et al, 2013), leads to phytoplankton and mesozooplankton diversity hotspots (Brandão et al, 2021; Ramond et al, 2021), which may, therefore, represent abundant trophic resources for planktivorous fish species (e.g., anchovies, pilchards; Brandão et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of submerged rocks and reefs (Hinschberger & Pauvret, 1968), makes this a dangerous area restricting fishing activities to hooks and lines. Moreover, the formation of the Ushant tidal front from May to October (Morin et al, 1985)—separating homogeneous coastal waters from the seasonally stratified offshore waters (Schultes et al, 2013)—influences primary productivity and planktonic communities in this area (Brandão et al, 2021). The Audierne Bay (southern part; Figure 1), extends from the Pointe du Raz to the Pointe de Penmarc'h in the Bay of Biscay.…”
Section: Methodsmentioning
confidence: 99%
“…Challenges and disadvantages of COI as a metabarcode include lack of universal primers and missing groups due to primer-mismatch (Deagle et al, 2014;Clarke et al, 2017;Hajibabaei et al, 2019). A number of studies have evaluated the results using COI metabarcodes based on parallel analysis using multiple metabarcode gene regions, including hypervariable regions of 18S rRNA (Djurhuus et al, 2018;Steffani et al, 2018;Giebner et al, 2020;Pitz et al, 2020;Brandão et al, 2021;Pappalardo et al, 2021;Questel et al, 2021;Zhao et al, 2021).…”
Section: Introduction Metabarcoding Of Zooplankton Diversitymentioning
confidence: 99%